La Machine: Obstetric Phantoms of Madame Du Coudray … Back to the Roots. (April 2022) - Scharf, Jann Lennard; Bringewatt, Arne; Dracopoulos, Christoph; Rody, Achim; Weichert, Jan; Gembicki, Michael
For 300 years now, obstetrics has drawn on the concept of simulation training to not only teach anatomy and physiology theoretically, but to literally infuse it practically. In an 18 th century scientific culture, which was predominantly patriarchal, the French royal midwife Angelique Marguerite Le Boursier du Coudray excelled in this field. Using La Machine, one of the first obstetric phantoms, she taught thousands of midwives and even physicians. The exponential increase in publications on obstetric simulations in recent years continues to underline their current relevance, and Madame du Coudray was once at the forefront with her mannequin, probably the most sophisticated phantom of its time, a symbiosis of practical-robust architecture and anatomical-theoretical accuracy. In retrospect, it is therefore worthwhile to take a closer look at this pioneer and her obstetric phantoms, applied in the first national simulation-based training course, and to evaluate them in the overall picture of the development of anatomically correct replicas for practice-oriented training with detailed, flexible exercise – back to the roots.